Arkeologi Pengetahuan Tayyib Tizini tentang Pluralitas Interpretasi Alquran - Marsyam, Abdul Waris (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2020)
This paper analyzes the thought of Tayyib Tizini, a Syrian nationalist philosopher, on archeology of knowledge of the plurality of the Qur’anic interpretations. Tizini is very keen to voice the plurality of Qur’anic interpretations along with the strong apparent of the coercion movement and the domination of a particular interpretation of religious texts. By using descriptive-analytic method with a philosophical-rationalistic approach, this paper concludes that the text of the Qur’an and the empirical reality of an internalized society (al-wad‘iyah al-mujtama‘ al-mushakhkhas) have an open structure that allows plurality of interpretations in accordance with the needs of humanity. Through Tizini’s archeological analysis, it is found two occurred channels in the activity of understanding the Qur’an. The first channel is limited by cognitive aspects which are also limited by the level of knowledge of the person who perceives it. The second channel presents itself in ideology which is related to material interests, political streams and ambitions, social conflicts, groups, classes, countries, nations and so on. These two channels are the two things that impose, both clandestinely and openly the process of, the emergence of a plurality of the Qur’anic interpretations.